Deep Talk: A Dialogic Instruction Method for Enhancing the Sense of Belonging - Aerila Juli-Anna; Kinossalo Maiju; Siipola Mari; Laaksonen Piia; Lamminen Anu; Valkonen Tuula (European Open Access Publishing, 2022)
In this study, we investigate Deep Talk, which is a method used in the context of early years education in Finland. The method is based on multisensory storytelling and clear phases. The method has received positive feedback from educators and children, but no prior research has been conducted on it. This data aims to determine the significant elements of the method for the individual child and the children in a group. The data consisted of 25 narrations of educators who participated in Deep Talk training and had been serving as Deep Talk instructors. The data were analyzed using a data- and theory-driven qualitative content analysis through the dialogical process of the research team. The results showed that Deep Talk consisted of several elements that had a positive effect on the sense of belonging, increasing the dialogue between children, getting children’s voices heard and reducing inner speech. These effects seemed to strengthen the benefits of the method beyond the Deep Talk sessions as the method is implemented more constantly among children.